Improved susceptibility weighted imaging method using multi‐echo acquisition. Issue 2 (16th September 2013) - Oh, Sung Suk; Oh, Se‐Hong; Nam, Yoonho; Han, Dongyeob; Stafford, Randall B.; Hwang, Jinyoung; Kim, Dong‐Hyun; Park, HyunWook; Lee, Jongho
<x xml:space="preserve">Abstract</x> Purpose To introduce novel acquisition and postprocessing approaches for susceptibility weighted imaging (SWI) to remove background field inhomogeneity artifacts in both magnitude and phase data. Methods The proposed method acquires three echoes in a three‐dimensional gradient echo (GRE) sequence, with a field compensation gradient (z‐shim gradient) applied to the third echo. The artifacts in the magnitude data are compensated by signal estimation from all three echoes. The artifacts in phase signals are removed by modeling the background phase distortions using Gaussians. The method was applied in vivo and compared with conventional SWI. Results The method successfully compensates for background field inhomogeneity artifacts in magnitude and phase images, and demonstrated improved SWI images. In particular, vessels in frontal lobe, which were not observed in conventional SWI, were identified in the proposed method. Conclusion The new method improves image quality in SWI by restoring signal in the frontal and temporal regions. Magn Reson Med 72:452–458, 2014. © 2013 Wiley Periodicals, Inc.